Plastics and sustainable piping systems - Chasis, David A., 1938- (Industrial Press, 2014)
Plastic piping is now the preferred material in countless applications -- municipal water and sewer lines, drain/waste/vent lines, and chemical waste drainage, to mention just a few -- because plastics are durable, easy and safe to install, environmentally sound, and cost-effective. This compendium of over 40 articles is written by a professional involved in plastic fluid handling products for over 45 years.